Improving the bulk gas transport of Fe-N-C platinum group metal-free nanofiber electrodes via electrospinning for fuel cell applications. (July 2020) - Kabir, Sadia; Medina, Samantha; Wang, Guanxiong; Bender, Guido; Pylypenko, Svitlana; Neyerlin, K.C.
Abstract: To overcome transport limitations associated with thicker platinum group metal-free (PGM-free) electrodes, it's imperative to investigate and tailor alternative electrode architectures to maximize the bulk electrode transport properties, whilst not significantly impeding electrocatalyst active site accessibility and electrode proton resistance. In this work, PGM-free nanofiber electrode mats, prepared by electrospinning a mixture of pyrolyzed Fe-N-C catalyst, Nafion ionomer and a carrier polymer Poly Acrylic acid (PAA), were compared to traditionally prepared electrodes. The morphological properties and elemental distribution of the fabricated nanofiber electrodes showed that the exterior surface of the PGM-free nanofibers was conformally covered with a thin ionomer film. Electrochemical diagnostics performed utilizing cyclic voltammetry, electrochemical impedance spectroscopy (EIS) and H2 -limiting current measurements, revealed an increase in electric double layer capacitance, reduction in electrode proton transport and a significant improvement in bulk-electrode gas transport properties for the nanofiber electrodes, supporting the observed performance increase from electrochemical polarization data obtained in H2 -O2 /Air fuel cells. At 100% RH in H2 /Air, the power density of the nanofiber electrodes increased ca. 50% vs. the traditionally prepared electrodes (ca. 260 vs 175 mW cm −2 ), which was attributed to a less tortuous molecular diffusion pathway and an associated reduction in the pressure dependent and independent gas transport resistances in the nanofiber electrodes. Graphical abstract: Image 1 Highlights: Electrospun nanofiber electrode fabricated with conformal ionomer coverage and macroporous network. Break-up of catalyst aggregates due to particle shearing under applied electric field. Increased capacitance and accessibility to active sites under high & low RH conditions. Inter-fiber voids in fiber mat significantly reduced bulk gas transport resistances. Less tortuous O2 molecular diffusion pathway and reduced Knudsen diffusion.